The Effect of Hypothermia Prevention Education on Mothers' Ability to Care for Newborns - Hanifah, Astin Nur; Nur, Armiyati (Asosiasi Guru dan Dosen Seluruh Indonesia, 2025)
Hypothermia is a serious problem in newborns that can increase morbidity and even neonatal mortality. Educating mothers is an important strategy to improve their ability to care for newborns and prevent hypothermia. This study aimed to determine the effect of hypothermia prevention education on mothers' ability to care for newborns. The research method used a pre-experimental design with a one-way approach. group pre-test Post-test. The study sample consisted of 40 post-partum mothers selected using a purposive sampling technique. The research instruments were a questionnaire and an observation sheet on newborn care skills. The results showed a significant increase in mothers' ability to care for newborns after being given education (p < 0.05). Education has been proven effective in improving mothers' skills in preventing hypothermia in newborns.